Experience in using the excimer laser-assisted nonocclusive anastomosis nonocclusive bypass technique for high-flow revascularization: Mannheim-Helsinki series of 64 patients - Vajkoczy, Peter; Schneider, Ulf Christoph; Schmiedek, Peter (Neurosurgery, 2012)
AbstractBACKGROUND. The excimer laser-assisted nonocclusive anastomosis (ELANA) technique enables large-caliber bypass revascularization without temporary occl
Published: 12 July 2011
Gesehen am 17.02.2019